SUMBER AKIDAH DAN AKHLAK DALAM PERSPEKTIF TURATS DAN EPISTEMOLOGI KONTEMPORER: STUDI KEPUSTAKAAN PENDIDIKAN ISLAM - Deti Yulia Martiana; Eka Putra Wirman; Hasnah (As-Sulthan Journal of Education, 2026)
Aqidah and akhlak education plays a fundamental role in shaping students’ character within Islamic education. However, the development of contemporary epistemology poses significant challenges in understanding the sources of aqidah and akhlak amid modern educational contexts. This study aims to analyze the sources of aqidah and akhlak from the perspective of Islamic turath and to examine their relevance to contemporary epistemology in Islamic education. This research adopts a qualitative approach using a literature review method, drawing on classical and contemporary Islamic scholarship as well as relevant academic journal articles. The findings indicate that, from the turath perspective, the sources of aqidah and akhlak are primarily derived from the Qur’an and Hadith, which have been systematically interpreted through Islamic scholarly traditions. Meanwhile, contemporary epistemology contributes methodological approaches that emphasize rationality, reflection, and contextual learning. Nevertheless, contemporary epistemology cannot function as an independent source of values; it must be critically integrated with Islamic teachings. The integration of turath and contemporary epistemology in aqidah and akhlak education enables the development of adaptive learning practices while preserving Islamic moral foundations. This study contributes theoretically to the discourse on epistemology in Islamic education.